2020
DOI: 10.3389/fphys.2020.566625
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alcohol Intake and Semen Parameters in Men With Primary and Secondary Infertility: A Cross-Sectional Study

Abstract: Alcohol consumption has commonly been associated with semen parameters. However, the association between alcohol intake and semen parameters in primary and secondary infertile men remains unclear. In this study, 776 infertile men from China were grouped according to alcohol intake: abstainers, moderate drinkers (<9 units/week, up to approximately 100 g of ethanol) and heavy drinkers (≥9 units/week). Semen parameters, including semen volume, sperm concentration, total sperm count, progressive motility and norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, a cross-sectional study including 8344 healthy men did not report any association between low/moderate alcohol consumption and semen quality [ 81 ]. Similarly, other studies failed to identify any coherent dose–response pattern in the semen parameters depending on the degree of alcohol consumption [ 83 , 88 , 132 , 133 , 134 ]. Boeri et al suggested that the correlation between alcohol consumption and alterations in the semen parameters might be directly proportional to the amount of alcohol consumed.…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, a cross-sectional study including 8344 healthy men did not report any association between low/moderate alcohol consumption and semen quality [ 81 ]. Similarly, other studies failed to identify any coherent dose–response pattern in the semen parameters depending on the degree of alcohol consumption [ 83 , 88 , 132 , 133 , 134 ]. Boeri et al suggested that the correlation between alcohol consumption and alterations in the semen parameters might be directly proportional to the amount of alcohol consumed.…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 97%
“…Several recent studies of different global geographic regions have confirmed the negative impact of heavy alcohol consumption on semen quality. In fact, in China, a cross-sectional study conducted in 2020 reported reduced sperm concentrations in 55 heavy drinkers suffering from secondary infertility [ 88 ], while in Italy, 45 heavy drinkers with primary infertility showed reduced sperm concentrations and motilities compared to moderate drinkers or abstainers [ 89 ]. Similarly, an inverse association between sperm counts and alcohol consumption was observed in a Brazilian population of 167 infertile men [ 90 ], while a large study conducted on a Danish population of 1221 men showed a direct association between worsening semen quality and increasing alcohol intake [ 92 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
“…A recent meta-analysis described how occasional alcohol intake is not considered to be a major risk factor, but daily use has been consistently linked to different sperm abnormalities including decreased semen volume, and worse sperm morphology (Ricci et al, 2017a). Moreover, Bai et al, in a study investigating 776 infertile men, observed that those reporting heavy alcohol consumption had a higher risk of abnormal sperm concentrations (Bai et al, 2020). These findings are additionally supported by Boeri et al's study of 189 infertile men that found heavy alcohol consumption led to worse semen quality than abstinence and moderate consumption (Boeri et al, 2019a).…”
Section: Medications and Substancesmentioning
confidence: 99%
“…Testosterone levels and sperm concentration decrease with age, although some aging men can still be fertile by attempting multiple intercourse ( 25 ). In addition, several cases of infertility may potentially be induced by occupational exposure to toxic chemicals and lifestyle factors including tobacco smoking ( 26 ) and alcohol intake ( 27 ), and psychological stress can cause endocrine disruptions leading to male infertility. Figure 1 shows all the causes and potential risks of male infertility.…”
Section: Causes Of Male Infertilitymentioning
confidence: 99%